Housing, land, and property restitution rights of refugees and displaced persons : laws, cases, and materials / edited by Scott Leckie. - Leckie, Scott (Cambridge University Press, 2007)
The legal recognition of the housing, land, and property rights of refugees and displaced persons has expanded steadily in recent years as the realization has grown that securing these rights will be beneficial to long-term peace, stability, economic vitality and justice. This volume, first published in 2007, contains more than 240 of the laws, cases and materials that have been adopted during the past century, which accord those unjustly and arbitrarily displaced from their homes and lands with rights: not simply to return to their countries or places of origin, but to return to the original home, land or property from which they were initially forced to flee. The breadth of the restitution standards found within this volume, combined with selected examples of case law and other materials, are a clear indication that a right to housing, land, and property restitution for refugees and displaced persons has emerged within the global legal domain.